In the end, it's only temporary - Lum, Jonathan Jie Le (Nanyang Technological University, 2024)
In the End It’s Only Temporary is an exploration of the intersection between dreams and lived experiences, examining how reality shapes the landscapes of our dreams. It explores the blurred boundaries between these realms, where our dream persona may diverge from our waking selves, revealing our intrinsic fears and desires.